PERTAMBANGAN MINERAL SEBAGAI PENUNJANG ENERGI BERKELANJUTAN YANG BERTENTANGAN DENGAN PRINSIP LINGKUNGAN HIDUP: TINJAUAN YURIDIS PUTUSAN PTUN JAKARTA NOMOR 59/G/LH/2023/PTUN.JKT - Dhiya Ghina Zhafira; Yayang Rizki Pratama; Najla Alyaa; Annisa Davina Paramitha; Tegar Putra Novandi; Roy Pasaribu (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Mineral mining holds strategic relevance in supporting the transition to sustainable energy, particularly through the utilization of metallic minerals such as zinc (Zn) and lead (Pb) as components in energy storage technologies. In practice, however, such activities frequently conflict with the principles of environmental protection embedded in national legislation. This study juridically analyzes the tension between the interests of mineral utilization for sustainable energy and compliance with environmental law principles, focusing on Jakarta Administrative Court (PTUN) Decision Number 59/G/LH/2023/PTUN.JKT, which annulled the Ministerial Decree of the Ministry of Environment and Forestry (KLHK) Number SK.854/MENLHK/SETJEN/PLA.4/8/2022 concerning the Environmental Feasibility of the Zinc and Lead Mining Activities of PT. Dairi Prima Mineral in Dairi Regency, North Sumatra. The study employs normative legal research methods with statutory, casebased, and conceptual approaches. The findings reveal that the issuance of the disputed environmental approval contained juridical defects, including violations of the principles of transparency, precaution, and noncompliance with the AMDAL assessment mechanism under Government Regulation Number 22 of 2021. The Jakarta PTUN decision affirmed the supremacy of environmental law in natural resource utilization, while simultaneously posing factual obstacles to the continuity of mining operations that contribute to the sustainable energy supply chain. These conditions underscore the urgent need for regulatory harmonization between national energy policy and environmental protection instruments to achieve genuinely sustainable mineral mining.